2018
DOI: 10.1089/ars.2017.7258
|View full text |Cite
|
Sign up to set email alerts
|

The NAD+-Dependent Family of Sirtuins in Cerebral Ischemia and Preconditioning

Abstract: Sirtuins are an evolutionarily conserved family of NAD-dependent lysine deacylases and ADP ribosylases. Their requirement for NAD as a cosubstrate allows them to act as metabolic sensors that couple changes in the energy status of the cell to changes in cellular physiological processes. NAD levels are affected by several NAD-producing and NAD-consuming pathways as well as by cellular respiration. Thus their intracellular levels are highly dynamic and are misregulated in a spectrum of metabolic disorders includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 190 publications
(304 reference statements)
0
46
0
3
Order By: Relevance
“…SIRT4 is strongly expressed in astrocytes in the postnatal brain (specifically in the mitochondria) and reduced during development [44]. It is worth mentioning that SIRT4 associates with cerebral ischemia [45]. SERPINH1, expressed in vascular smooth muscle cells of the brain, is involved in atherosclerosis [46].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT4 is strongly expressed in astrocytes in the postnatal brain (specifically in the mitochondria) and reduced during development [44]. It is worth mentioning that SIRT4 associates with cerebral ischemia [45]. SERPINH1, expressed in vascular smooth muscle cells of the brain, is involved in atherosclerosis [46].…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that SIRT1 activation was necessary for NH neuroprotection, although this drug composition targets multiple proteins 5 . SIRT1 has been shown to be important for neuroprotection in several models of neurodegenerative diseases (e.g., Alzheimer’s disease, Huntington’s disease) 29 31 and is crucial in cerebral ischemia and preconditioning 32 . We demonstrated herein that either NH-induced activation or overexpression of SIRT1 boost endogenous mechanisms of neuroprotection after injury, as it is the ATF6-GRP78 branch of UPR 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuins are homologs of yeast silent information regulator 2 (Sir2). Sir2 has attracted the attention of researchers given its involvement in longevity ( 1 ). The mammalian sirtuins (SIRT1-7) have different subcellular localizations.…”
Section: Introductionmentioning
confidence: 99%
“…In glycolysis, NAD + is reduced to NADH. In oxidative phosphorylation and cellular respiration, NADH is oxidized to NAD + by electron transport chain (ETC) ( 1 ). As such, NAD + concentrations fluctuate with cellular metabolic status and nutrient availability.…”
Section: Introductionmentioning
confidence: 99%